2009
DOI: 10.1117/12.814000
|View full text |Cite
|
Sign up to set email alerts
|

Pattern decomposition and process integration of self-aligned double patterning for 30nm node NAND FLASH process and beyond

Abstract: As IC manufacturing goes from 45nm to 30nm node half-pitch, the lithography process k1 factor will fall below 0.25 by using water-based ArF-immersion scanner. To bridge the gap between ArF-immersion and next generation lithography, which is not ready yet for production, Double Patterning Technology (DPT) has been evaluated and identified as a promising solution as it utilizes existing equipment and processes. Self Aligned Double Patterning (SADP) has the advantage of dense array definition without overlay issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Among various DPT schemes, SADP has the advantage of excellent overlay performance in pitch splitting, and is therefore very useful for manufacturing devices with regular dense patterns, such as FLASH memory devices. Even though the nature of SADP restricts its freedom of 2-D or through-pitch pattern definition, recent studies [2,3] have demonstrated the capability of implementing SADP on both DRAM and logic layouts with the adoption of gridded or non-gridded design rule, as schematically shown in Figs.1 and 2. In SPIE 2009 [3], we had demonstrated the ideas of 30nm node NAND FLASH cell circuit critical feature definition by decomposing the target patterns to SADP defined dense array in conjunction with cropping and/or periphery masks steps, based on manual design.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among various DPT schemes, SADP has the advantage of excellent overlay performance in pitch splitting, and is therefore very useful for manufacturing devices with regular dense patterns, such as FLASH memory devices. Even though the nature of SADP restricts its freedom of 2-D or through-pitch pattern definition, recent studies [2,3] have demonstrated the capability of implementing SADP on both DRAM and logic layouts with the adoption of gridded or non-gridded design rule, as schematically shown in Figs.1 and 2. In SPIE 2009 [3], we had demonstrated the ideas of 30nm node NAND FLASH cell circuit critical feature definition by decomposing the target patterns to SADP defined dense array in conjunction with cropping and/or periphery masks steps, based on manual design.…”
Section: Introductionmentioning
confidence: 98%
“…Even though the nature of SADP restricts its freedom of 2-D or through-pitch pattern definition, recent studies [2,3] have demonstrated the capability of implementing SADP on both DRAM and logic layouts with the adoption of gridded or non-gridded design rule, as schematically shown in Figs.1 and 2. In SPIE 2009 [3], we had demonstrated the ideas of 30nm node NAND FLASH cell circuit critical feature definition by decomposing the target patterns to SADP defined dense array in conjunction with cropping and/or periphery masks steps, based on manual design. In this paper, we extend the previous works on manual-based decomposition to a more sophisticated use on full-area NAND FLASH critical layer layout decomposition by utilizing an automated electronic design (EDA) tool.…”
Section: Introductionmentioning
confidence: 98%